Lymphatic Filariasis Disseminating to the Upper Extremity. (19th February 2014) - Maldjian, Catherine; Khanna, Vineet; Tandon, Bevan; Then, Matthew; Yassin, Mohamed; Adam, Richard; Klein, Michael J.
Abstract : Lymphatic filariasis is the most common cause of acquired lymphedema worldwide (Szuba and Rockson, 1998). It is endemic to tropical and subtropical regions, and its effects are devastating. With over 100 million infected persons, it ranks second only to leprosy as the leading cause of permanent and long-term disability. Wuchereria bancrofti is the etiologic agent in 90% of cases. There is a dearth of published MRI findings with pathologically proven active infections, making this entity even more of a diagnostic dilemma. Imaging may provide the first clue that one is dealing with a parasite and may facilitate proper treatment and containment of this disease. This is the first report of pathologic correlation with MRI findings in the extremity in active filariasis. The magnetic resonance images demonstrate an enhancing, infiltrative, mass-like appearance with partial encasement of vasculature that has not been previously described in filariasis. Low signal strands in T2-hyperintense dilated lymphatic channels are seen and may depict live adult worms. We hypothesize that the low signal strands correspond to the collagen rich acellular cuticle. This, in combination with the surrounding hyperintense T2 signal, corresponding to a dilated lymphatic channel, may provide more specific MRI findings for active nematodal infection, which can prompt early biopsy, pathological correlation, and diagnosis.